Implemantasi Nilai -Nilai Pendidikan Karakter QS Al-Hujurat Ayat 11-13 di Era Digital pada Peserta Didik Kelas III SDIT Ihyaussunnah Bontang Tahun Pelajaran 2023/2024 - Wahyuni, Sri; Ikrar, Ikrar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to understand and find out the Implementation of Character Education Values QS Al-Hujurat verses 11-13 in the Digital Age. This surah is an affirmation as well as a guide for all human beings from various walks of life on the importance of ethics, manners, and character, especially in the digital era in associating in the surrounding environment, both with fellow Muslims and non-Muslims, so that a stable condition will be created between hablun minallahi and hablun minannasi. The method used is qualitative. The focus of research on class III students. Data collection techniques through observation, interviews and documentation. The results showed that QS Al-Hujurat verses 11-13 which are carried out properly will provide direction, teaching and control of educators so that students feel closer to God, avoid prejudice, respect and tolerance for each other so that a comfortable atmosphere grows in the environment, especially in the digital era. It can be concluded that the values of character education in QS Al-Hujurat verses 11-13 in the digital era can provide guidance to students because it contains three educational values such as the value of character education respecting each other, the value of education to be kind, the value of tolerance education.